Application of Single MEMS-accelerometer to Measure 3-axis Vibrations and 2-axis Tilt-Angle Simultaneously - Didik R. Santoso; Sukir Maryanto; Ahmad Nadhir (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This paper discusses a technique of developing an integrated sensor system, to measure the mechanical vibrations in 3-axis and the tilt-angle in 2-axis simultaneously, using only single MEMS-accelerometer. Type of MEMS-accelerometer that used in this experiment is MMA7361L, which is an analog-type acceleration sensor in the form of MEMS, with a maximum sensitivity of 800 mV/g. The MMA7361L has three outputs of voltage (Vx, Vy, Vz) in response to the acceleration value "g" of each working-axis corresponding vibrating (gx, gy, gz). By using certain techniques in the design of signal conditioning circuits, then the MMA7361L can be used to detect parameters of the vibration in 3-axis and the tilt-angle in 2-axis at the same time, simultaneously. To accommodate five output signal of the sensor system, used a data acquisition system that was built based on PIC16F876 microcontroller, which are already contained five internal ADC with 10 bits resolution. Thus, the resulting integrated sensor system becomes very simple, minimal components, and inexpensive. The experimental results show that the developed integrated sensor system has capability to measure the 3-axis vibrations and the 2-axis tilt-angle, with fairly good accuracy.